ANALISIS PROSES PELAKSANAAN ANGGARAN DANA BANTUAN OPERASIONAL KESEHATAN (BOK) PADA DINAS KESEHATAN KABUPATEN BUOL - Balgis, Balgis; Muslimin, Muslimin; Yusnita, Nina (Katalogis, 2018)
The research is aimed to determine the process of execution of health operational funds that includes some steps: planning, disbursement, distribution and accountability, and reporting. The research is qualitative with study case approach. It defines 18 informants, people who are responsible for managing the health operational funds, with purposive sampling technique. The study results show that the planning process is not on target due to the late publication of the guidelines, which slows down the budget execution. The human resource is lack of competency in managing the process, and also lack of coordination and miscommunication occurred in the process of budget verification. The department, and the other one is done in the PPKAD. Delay in funds’ disbursement in the beginning of the year has caused health centers are overwhelmed in preparing paper works of accountability. Alternative solution or recommendation of this study is the need to prepare adequate human resources, regulation according to the needs, and standard operating procedures in the implementation of related activities.